Based on Arduino Design of Intelligent Exploration Vehicles. Issue 1 (1st April 2022) - Liu, Zhijun; Yang, Chenglong; Xi, Wen
Abstract: This paper details the design and implementation of the hardware circuit of the intelligent cart motion control system, and uses a variety of virtual reality and visual sensing technologies to design an environmental detection and search and rescue robot under complex conditions. Infrared technology is used to achieve the function of automatic obstacle avoidance of the trolley, ultrasonic technology is used to achieve the function of distance measurement, Bluetooth is used to achieve the function of wireless remote control of the trolley, GPS technology is used to display the geographical position of the trolley, a homemade bionic robotic arm is installed, and the robotic arm servo can be controlled by PC upper computer, Bluetooth and homemade body remote sensing controller to work to achieve the removal of obstacles and unknown environment and dangerous areas The information is collected through a PC, Bluetooth and a home-made body telemetry controller.